Mutation of SHOC2 promotes aberrant protein N-myristoylation and causes Noonan-like syndrome with loose anagen hair - Cordeddu, Viviana; Di Schiavi, Elia; Pennacchio, Len A; Ma'ayan, Avi; Sarkozy, Anna; Fodale, Valentina; Cecchetti, Serena; Cardinale, Alessio; Martin, Joel; Schackwitz, Wendy; Lipzen, Anna; Zampino, Giuseppe; et al. (Nature genetics, 2009)
Marco Tartaglia and colleagues report the identification of mutations of SHOC2 in individuals with Noonan-like syndrome with loose anagen hair. The mutations cause aberrantly acquired N-myristoylation of SHOC2 resulting in aberrant targeting of SHOC2 to the plasma membrane. SHOC2 is believed to function as a scaffold linking RAS to downstream signal transducers. N-myristoylation is a common form of co-translational protein fatty acylation resulting from the attachment of myristate to a required N-terminal glycine residue 1 , 2 . We show that aberrantly acquired N-myristoylation of SHOC2, a leucine-rich repeat–containing protein that positively modulates RAS-MAPK signal flow 3 , 4 , 5 , 6 , underlies a clinically distinctive condition of the neuro-cardio-facial-cutaneous disorders family. Twenty-five subjects with a relatively consistent phenotype previously termed Noonan-like syndrome with loose anagen hair (MIM607721) 7 shared the 4A>G missense change in SHOC2 (producing an S2G amino acid substitution) that introduces an N-myristoylation site, resulting in aberrant targeting of SHOC2 to the plasma membrane and impaired translocation to the nucleus upon growth factor stimulation. Expression of SHOC2 S2G in vitro enhanced MAPK activation in a cell type–specific fashion. Induction of SHOC2 S2G in Caenorhabditis elegans engendered protruding vulva, a neomorphic phenotype previously associated with aberrant signaling. These results document the first example of an acquired N-terminal lipid modification of a protein causing human disease.